IMPLMENTASI TOOLS GOOGLE CLASSROOM PADA MATA_KULIAH QOWAIDUL FIQHIYAH_PROGRAM_STUDI_PERBANKAN SYARIAH FAKULTAS EKONOMI UNIVERSITAS ISLAM MALANG - Oby Khairul (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The development of science and information technology isrankindicationpoflthemprogress ofbhumanxcivilization. One function of information technology is to make it easier for humans to access material around the world quickly. With various facilities thatacanvbe taken. In thezcontextbofzeducation, forpexample, current learning is not only focused on classrooms, but can be accessed through online-based information tools. In studying at the Islamic University of Malang, for example, students who are oriented toward majors who are capable and very competitive in terms of assessing employment say that universities only rely on very limited class meetings. There is a possibility that shows the absence of a lecture process such as the distance at which students live far from campus, poor physical conditions or other possibilities that force students not to take part in college activities. In the context of education, especially in Indonesia, the Kata Kunci: Teknologi Pendidikan, e-Learning, LMS, Google Classroom, Media Pembelajaran.